Impacts of dance on non-motor symptoms, participation, and quality of life in Parkinson disease and healthy older adults. Issue 4 (December 2015) - McNeely, M.E.; Duncan, R.P.; Earhart, G.M.
Highlights: We review the effects of dance on non-motor functions in older adults and PD. Participation, quality of life, mood, cognition and non-motor functions are analyzed. Knowledge gaps, limitations, and opportunities for further study are identified. Some, but not all, studies indicate dance may improve some non-motor functions. Abstract: Evidence indicates exercise is beneficial for motor and non-motor function in older adults and people with chronic diseases including Parkinson disease (PD). Dance may be a relevant form of exercise in PD and older adults due to social factors and accessibility. People with PD experience motor and non-motor symptoms, but treatments, interventions, and assessments often focus more on motor symptoms. Similar non-motor symptoms also occur in older adults. While it is well-known that dance may improve motor outcomes, it is less clear how dance affects non-motor symptoms. This review aims to describe the effects of dance interventions on non-motor symptoms in older adults and PD, highlights limitations of the literature, and identifies opportunities for future research. Overall, intervention parameters, study designs, and outcome measures differ widely, limiting comparisons across studies. Results are mixed in both populations, but evidence supports the potential for dance to improve mood, cognition, and quality of life in PD and healthy older adults. Participation and non-motor symptoms like sleep disturbances, pain, and fatigue have not been measured in older adults. Additional well-designed studies comparing dance and exercise interventions are needed to clarify the effects of dance on non-motor function and establish recommendations for these populations.